Role of Surgery in Management of Osteo-Articular Tuberculosis of the Foot and Ankle - Dhillon, Mandeep Singh (Open Orthop J, 2017)
BACKGROUND: Tuberculosis of the foot and ankle still remains to be a significant problem, especially in the developing countries, and with an increase in incidence in immunosuppressed patients. Treatment is mainly medical using multidrug chemotherapy; surgical interventions range from biopsy, synovectomy and debridement, to joint preserving procedures like distraction in early cases, and arthrodesis of hindfoot joints and the ankle in advanced disease with joint destruction. Surgical Options: All procedures should be done after initiating appropriate medical management. The ankle is the commonest joint needing intervention, followed by the subtalar and talo-navicular joint. Forefoot TB limited to the bone rarely needs surgical intervention except when the infective focus is threatening to invade a joint. Articular disease can spread rapidly, so early diagnosis and treatment can influence the outcome. Surgical interventions may need to be modified in the presence of sinuses and active disease; fusions need compression, and implants have to be chosen wisely. External fixators are the commonest devices used for compression in active disease, but intramedullary nails better stabilize pantalar arthrodesis. Arthroscopy has become a valuable tool for visualizing the ankle and hindfoot joints, and is an excellent adjunct for arthrodesis by minimally invasive methods. CONCLUSION: Although Osteoarticular Tb involving the foot and ankle is largely managed with chemotherapy, specific indications for surgical intervention exist. Timely done procedures could limit joint destruction, or prevent spread to adjacent joints. Fusions are the commonest procedure for sequelae of disease or for correcting residual deformity.